Silyl formates as hydrosilane surrogates for the transfer hydrosilylation of ketones. Issue 43 (6th May 2022) - Romero, R. Martin; Thyagarajan, Neethu; Hellou, Nora; Chauvier, Clément; Godou, Timothé; Anthore-Dalion, Lucile; Cantat, Thibault
Abstract : The transfer hydrosilylation of ketones with silyl formates was unlocked, relying on the crucial role of a cooperative PN H P ligand. Abstract : A transfer hydrosilylation of ketones employing silyl formates as hydrosilane surrogates under mild conditions is presented. A total of 24 examples of ketones have been successfully converted to their corresponding silyl ethers with 61–99% yields in the presence of a PN H P-based ruthenium catalyst and silyl formate reagent. The crucial role of the ligand for the transformation is demonstrated.